2016
DOI: 10.1021/acs.iecr.5b04906
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Carbon Capture through Incorporation of Surfactant Additives

Abstract: The CO 2 absorption properties of monoethanolamine (MEA) solutions containing varying amounts of surfactant were examined using different experimental apparatus: a packed column, a stirred reactor, a wetted wall column, and a bubble column. The carbon capture efficiency in the packed column was improved by the addition of surfactant. Surface tension measurements of the different solutions were taken over a range of CO 2 loadings, and the addition of surfactant was seen to lower the surface tension of the amine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The surfactant-like activity of 1 in solutions of MEA make determining the source of any enhancement difficult to isolate, although previous studies have shown the addition of surfactants to capture solutions may cause formation of a single layer film on the surface that blocks CO2 gas diffusion into the liquid and artificially depress the local amine concentration, decreasing overall mass transfer. 55 However, the constant surface tension and elasticity in solutions of A2P/AMP and A2P/AMP + 1 indicates there is no surfactant-like activity in this solvent blend and any enhancement is likely a result of the catalyst performing as designed. The lack of correlation between the surface properties and capture efficiency in these solutions seems counterintuitive when compared to traditional models of mass transfer in these systems, however as other recent work has shown, caution must be taken when predicting improvements based on fundamental and idealized laboratory testing methods, as counter-intuitive behavior was observed upon the addition of surfactants to stirred-reactor experiments with a flat gas/liquid interface, 55 much like the wetted-wall experiments here.…”
Section: Determination Of Co2 Removal Ratementioning
confidence: 99%
See 2 more Smart Citations
“…The surfactant-like activity of 1 in solutions of MEA make determining the source of any enhancement difficult to isolate, although previous studies have shown the addition of surfactants to capture solutions may cause formation of a single layer film on the surface that blocks CO2 gas diffusion into the liquid and artificially depress the local amine concentration, decreasing overall mass transfer. 55 However, the constant surface tension and elasticity in solutions of A2P/AMP and A2P/AMP + 1 indicates there is no surfactant-like activity in this solvent blend and any enhancement is likely a result of the catalyst performing as designed. The lack of correlation between the surface properties and capture efficiency in these solutions seems counterintuitive when compared to traditional models of mass transfer in these systems, however as other recent work has shown, caution must be taken when predicting improvements based on fundamental and idealized laboratory testing methods, as counter-intuitive behavior was observed upon the addition of surfactants to stirred-reactor experiments with a flat gas/liquid interface, 55 much like the wetted-wall experiments here.…”
Section: Determination Of Co2 Removal Ratementioning
confidence: 99%
“…55 However, the constant surface tension and elasticity in solutions of A2P/AMP and A2P/AMP + 1 indicates there is no surfactant-like activity in this solvent blend and any enhancement is likely a result of the catalyst performing as designed. The lack of correlation between the surface properties and capture efficiency in these solutions seems counterintuitive when compared to traditional models of mass transfer in these systems, however as other recent work has shown, caution must be taken when predicting improvements based on fundamental and idealized laboratory testing methods, as counter-intuitive behavior was observed upon the addition of surfactants to stirred-reactor experiments with a flat gas/liquid interface, 55 much like the wetted-wall experiments here. We previously concluded that although the addition of surfactant lowers surface tension of the solution, it does not serve to promote bulk solvent mixing on its own in these flat interface systems.…”
Section: Determination Of Co2 Removal Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these concentrated C3P at the interface may affect CO 2 diffusion from the gas phase to the bulk solution phase. 36 Having a lower MEA concentration at the interface also decreases CO 2 reaction rate at the surface. Note that the slightly smaller MEA concentration and slightly larger water concentration at the vapor−liquid interface are in contrast to their respective concentrations around the C3P catalyst molecule in the bulk solution (see below).…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…This aggregation may be expected to hinder the accessibility of some C3P molecules to CO 2 or other reactants and decrease the catalyst performance. This catalyst aggregation, combined with the possibility of surface blocking of CO 2 diffusion, 36 9. As shown in Figure 9b, CO 2 and MEA exhibit maximum peak densities at r = 7.5 Å, which is roughly the size of one C3P molecule (Figure 9a).…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%